Achievement Motivation and Student Engagement: A Quantitative Correlational Study of Vocational High School Students - Partycia, Prayoga; Ade, Frihapma Semita; Kurniawan, Harri (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2025)
This study aims to examine the relationship between achievement motivation and student engagement among vocational high school students in Padang. A quantitative correlational approach was used, with a sample of 182 students selected through proportionate stratified random sampling. The instruments employed were the Achievement Motivation Scale and the Student Engagement Scale. The validity coefficients for the achievement motivation scale ranged from 0.310 to 0.750, with a reliability coefficient of 0.933. For the student engagement scale, the validity coefficients ranged from 0.330 to 0.617, and the reliability coefficient was 0.880. Data were analyzed using Pearson Product-Moment correlation. The results revealed a significant positive correlation (r = 0.558, p < 0.01), indicating that students with higher achievement motivation tend to have higher levels of engagement. The effective contribution of achievement motivation to student engagement was 31%. These findings suggest that internal motivation plays a substantial role in enhancing academic involvement among vocational students.